HYDROACOUSTIC OBSERVATIONS OF WEAK EARTHQUAKES IN SHALLOW WATERS OF THE SOUTHERN KURIL ISLANDS - Alexander S. Borisov; Sergey A. Borisov; Boris W. Levin; Elena V. Sarosova (Геодинамика и тектонофизика, 2015)
Results of hydroacoustic observations of signals from weak earthquakes in natural conditions in the region of the Southern Kuril Islands are presented. Some earthquakes were registered by the the Yuzhno-Kurilsk Seismic Station, other were only recorded by hydrophone stations. The observations were specific as seismic signals were recorded in shallow waters, i.e. in high noise level conditions. Hydrophones were installed in Lake Lagunnoe (Kunashir) and Khromovaya Bay (Shikotan). Our analysis of hydroacoustic records received from the hydrophone stations revealed no evident precursory response of the geological medium to weak distant events. This means that neither before the period of earthquake preparation nor during the earthquake preparation period, any geoacoustic emission was not detected. It is shown that despite the unfavourable noise level conditions, even distant weak earthquakes can be confidently registered by hydrophone stations, and pending application of proper signal processing techniques, it can be possible to determine arrival times of seismic waves and to measure parameters of seismic waves. It is also established that the frequency spectrum of acoustic signals from the weak earthquakes recordable by the hydrophone stations is continuous and of noise type in the frequency range up to 90–100 Hz. It is revealed that in some cases, weak earthquakes and microearthquakes may be forerun by low frequency signals.